PENAMAAN TEMPAT USAHA DI TANGERANG SELATAN: KAJIAN SEMANTIK - Sugiyo Sugiyo; Adinda Destiana Aisyah; Yasir Mubarok (Jurnal Semantik, 2023)
The purpose of this research is to analyze the naming of business places in South Tangerang. The theory used in analyzing naming is Chaer's theory (2009). This study uses a qualitative research model. The data collection process carried out in this study used the documentation method, followed by the observing and noting method. The data in this study are presented in a descriptive form or informal method. Based on the results of this study it was found that from 35 data on the naming of business places in South Tangerang, there were grammatical, lexical, and connotative meanings. In addition, the naming process that occurs in 35 data on the naming of business premises in South Tangerang, produces 23 data based on inventors or makers, 2 data based on characteristics, 4 data based on new names, 2 data based on place of origin, 1 data based on material, 1 data based on owner and shortening, 1 data based on new naming and owner, 1 data based on uniqueness and new naming. So, it can be concluded that the naming of business places in South Tangerang is dominated by the process of the inventor or maker because most of the business places use the name of the owner or maker.